Neuf ans d'études shīʿites (2009-2017): Bilan et perspectives - Terrier, Mathieu (Studia Islamica, 2018)
This article purports to report, without claiming to be exhaustive, on the recent dynamism within Shīʿi studies and their echoes throughout the various fields of Islamology. The first part will present a brief history of Shīʿi studies and the successive biases that have affected them. The second part will retrace the course of these studies over nine years (2009-2017), focusing on three collective works that rehabilitate in different ways Henry Corbin's analyses (m. 1979), considered outdated by some. The third part will address three areas in which recent Shīʿi studies have proved particularly fruitful: the history of early Islam; the intra-Shīʿi minorities and the origins of Islam; Islamic philosophy after Averroes (d. 1198). The sum total will reflect a decompartmentalisation of Shīʿi studies both internally, between the different currents and aspects of Shīʿism, and externally, between Shīʿism and Sunnism, philosophy or Sufism.